PENGARUH PERENCANAAN KERJA, MOTIVASI KERJA DAN KOORDINASI KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Yulihardi, Yulihardi; Iskamto, Dedi (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This study aims to analyze, Influence Work Planning, Work Motivation, and Work Coordination either partially or jointly to the Performance of North Sipora Subdistrict, Mentawai Islands District. The main problem in this research is "Performance of North Sipora Sub-district of Mentawai Islands Regency. The variables in this research are Work Planning, Work Motivation and Work Coordination (as independent variable) and Employee Performance (as dependent variable). The method used in this study is a survey method, with a population of 47 employees and a sample of 39 employees who are staff. The conclusion from the research that the hypothesis together and partially from the variables of Work Planning, Work Motivation and Work Coordination proved to have a positive and significant influence on the Performance of North Sipora Sub-District employee Mentawai Islands District as for the contribution of these three variables is 56,30% where motivation Work as the most dominant variable. Suggestions To focus more on improving work planning and coordination of work variables by taking into account the indicators. Creative, Innovative, adaptive, procedural and systematic for work planning. As well as communication model, how to convey instruction (command), and Ability to Accommodate an Interest for work coordination variable